Lipids in the Ocean 2021 - Domingues, Maria do Rosário; Soudant, Philippe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Lipids represent the major players in marine organisms as the major constituents of biological membranes, with key roles in biological processes and acclimation to environmental changes. New research trends aim to contribute to improving knowledge on the role lipids in the biological matrix, understanding the impact of climate change in marine organisms, and developing new tools for chemophenotyping, traceability, and biomarkers of trophic chains in marine ecosystems, such that the nutritional value or prospective bioactive compounds can be disclosed for health applications. "Lipids in the Ocean 2021" (http://lipids2021.web.ua.pt) was originally planned to be held at the University of Aveiro and ran from 5 to 7 July 2021 (and was ultimately an online conference due to uncertainties regarding the COVID-19 situation). The aim was to go in deep into research interests covering topics related to lipids from marine organisms, such as marine lipidomics, lipids as biomarkers in trophic webs, green lipids from the ocean (seaweeds, microalgae, and macrophytes), marine lipid biotechnology, and seafood traceability using lipids-from basic research to sustainable production and applications in the food, nutraceutics, feed, cosmetics, and pharma industries. This Special Issue welcomed not only attendees of "Lipids in the Ocean 2021" to publish their latest research outcomes but also all researchers in relevant fields to share their exciting works with the community.